The Role of Styles in Interiors - Safarova Nasiba Normatovna (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2025)
The exploration of interior design styles serves as a vital lens through which the intricacies of human experience within built environments can be understood. This essay, titled The Role of Styles in Interiors, aims to illuminate how various design styles influence not only aesthetic appeal but also emotional and psychological well-being. The significance of color, for instance, is emphasized in contemporary research, asserting that color profoundly impacts occupant experiences, enhancing mood and behavior, and thereby rendering spaces more habitable (Datta T et al., 2024). Additionally, as society progresses, the demand for both comfort and aesthetic form in our living environments grows, prompting a shift from mere functionality to a more holistic design approach that encompasses beauty and emotional resonance (Pan J et al., 2023). Consequently, this essay endeavors to analyze these styles in depth, revealing their integral role in shaping our daily experiences and surroundings.